PENGARUH PENERIMAAN DIRI TERHADAP OPTIMISME MAHASISWA TINGKAT AKHIR - Mardhatika, Arini; Rozi , Fahrul (Jurnal Ilmiah Penelitian Psikologi, 2022)
Compiling a final project or thesis is one of the requirements that must be met by every final- year student who wants to complete his lecture studies. Not infrequently during the process of completing the final project there are several obstacles which if not handled properly will trigger stress to an uncontrollable situation. This needs to be anticipated from every student by having an optimistic attitude in him. This study intends to examine how the influence of self-acceptance on the optimism of final year students who are writing a thesis. Researchers suspect that there is a significant influence between self-acceptance and optimism of final year students. In this study, there were 105 final year students who were writing a thesis, including 17 men and 88 women. Each respondent filled out two research instruments consisting of the Child and Adolescent Survey of Self-Acceptance (2012) and Life Orientation Test-Revised (1994). Based on the results of a simple regression test with SPSS Statistics 26 ver, it was obtained that the R square coefficient was 0.141, the beta coefficient was 0.95, and the probability value was 0.000 (p <0.01) which showed that there was a contribution of self-acceptance to optimism of 14.1%. and 85.9% contribution of other variables unknown to the researcher. It also shows that the researcher accepts the Alternative Hypothesis (Ha) and rejects the Null Hypothesis (H0), which means that there is a significant positive effect between self-acceptance and optimism for final year students. This shows that the higher the student's self-acceptance, the higher the optimism they have.